Factors associated with short sleep duration in adolescents - Filipin D.* (2016)
© 2015 Sociedade de Pediatria de São Paulo.Objective This study aimed to investigate the prevalence and factors associated with short sleep duration in adolescents from Maravilha - Santa Catarina (SC), southern Brazil. Methods The sample consisted of 516 adolescents aged 10-19 years of both genders. Issues associated with short sleep duration and difficulty falling asleep, chronotype, daytime sleepiness, physical activity, sedentary behavior and weight status were investigated. Results The prevalence of short sleep duration (<8h on school days) was 53.6%. Adolescents aged 17-19 years showed a 2.05-fold (95%CI: 1.20-3.50) greater prevalence of short sleep duration than those aged 10-12 years. The ones studying in morning and evening shifts had a higher prevalence of short sleep duration compared to those in the afternoon shift. Older age and school shift were the main factors associated with short sleep duration. Conclusions Adolescents from Maravilha showed high prevalence of short sleep duration, and older adolescents that studied in the morning and evening shifts showed reduced sleep.